A territorialização da luta pela terra no assentamento Matão no município de Porto Nacional/Ipueiras – TO - Souza, Rayanne Costa de (Universidade Federal do Tocantins, 2024)
These are reflections from the Social Movements research project in the municipality of Porto Nacional-To and aims to reflect on the Territorialization process of the struggle for land in the State of Tocantins and political actions of the Landless Workers Movement - MST. At the center of these conflicts is the territorial dispute that manifests itself in the control of the process of creation and destruction of the peasantry. The agrarian question is therefore a territorial question and agrarian reform is the face of this dimension. Conflicts express the clashes of structural processes and their conjunctural characteristics. In the last four decades, the agrarian question had different conjunctures. In the 1970s, the intensification of the expansion of monocultures and the expansion of agro-industry, accompanied by the near extinction of peasant movements due to the repression of the military dictatorship, marked one of the greatest crises of peasant resistance. With the redemocratization of the country in the 1980s, the consolidation of the agro-export and agro-industrial model took place simultaneously with the territorialization process of the struggle for land, with the increase in land occupations and the struggle for agrarian reform. The research was carried out at the “Unidos para Vencer” camp, where they were currently moved to a property located between the municipality of Ipueiras-To and Porto Nacional. The methodology adopted was interviews with some settlers and readings of articles on the present subject.